ANALISIS PENGGUNAAN MEDIA KAHOOT DALAM PEMBELAJARAN PPKN SERTA IMPLIKASINYA TERHADAP MINAT BELAJAR SISWA DI SMPN 1 BANDUNG TULUNGAGUNG - Febriana, Chrysta; Agustina Rahayu, Dwi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the use of Kahoot media in Civic Education (PPKn) learning and its implications for students' learning interest at SMPN 1 Bandung Tulungagung. The research employed a qualitative descriptive approach. Data were collected through observation, interviews, and documentation involving PPKn teachers and students. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results showed that the implementation of Kahoot in PPKn learning was carried out through planning, implementation, and evaluation stages. Kahoot was used as an interactive learning medium and evaluation tool that increased student participation during the learning process. Students showed positive responses characterized by enthusiasm, active participation, and greater engagement in learning activities. The use of Kahoot also had positive implications for students' learning interest, including increased attention, curiosity, motivation, and enjoyment in participating in PPKn learning. Therefore, Kahoot can be an effective digital learning medium to create a more interactive and meaningful learning environment.